Compatibility principle in the Tanyu Tongzhi Formula revealed by a cell-based analysis. (1st March 2019) - Ma, Lan; Zhang, Xue; Xu, Xiaoming; Ke, Yuehai; Dai, Jin; Cheng, Hongqiang; Mao, Wei
Abstract: Ethnopharmacological relevance: The concept of the prescription in Traditional Chinese Medicine (TCM) is usually characterized by the compatibility principle "monarch, minister, assistant, and guide", which means herbs play primary, secondary, auxiliary, or harmonic roles, respectively, to achieve the optimally holistic effect. Following this compatibility principle, the Tanyu Tongzhi Formula (TTF), used for many years to treat cardiovascular diseases, has been proved effective clinically and experimentally. Aim of the study: The ancient compatibility principle is based on experiences, but whether its underlying interactions can be explained at the cellular level is unknown. We aimed to explore the mechanisms of activity of the TTF herbs and the interactions between them. Materials and methods: We used a real-time cell analyzer to record the responses of COS-7 cells to the herbs in TTF, both individually and in different combinations. We also used biochemical assays to further characterize the TTF activity. Results: Monarch herb Fructus trichosanthis acts as an inhibitor of the EGF signaling. It's cytotoxicity, derived from inhibition of tubulin polymerization, could be completely neutralized by the combination of the phlegm group, or the whole TTF combination. Meanwhile, the minister, assistant, and guide herbs in the TTF did not affect EGF signaling. Conclusion: Our results provide a demonstration, at the cellular level, of the compatibility principle of "monarch, minister, assistant, and guide" in TTF. Under the guidance of this principle, TTF exerts the anti-inflammation and anti-tumor effects through inhibiting EGF signaling, while avoiding the microtubule-disrupting activity of Fructus trichosanthis. Graphical abstract: